If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3z + -6 = 0 Reorder the terms: -6 + -3z = 0 Solving -6 + -3z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -3z = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -3z = 0 + 6 -3z = 0 + 6 Combine like terms: 0 + 6 = 6 -3z = 6 Divide each side by '-3'. z = -2 Simplifying z = -2
| 8=-8x-8 | | 5(0)-y=-7 | | -9=-5x+19 | | 9e^3x+2=54 | | 7(x+2)=(5x+1)/2 | | (x+2)=(5x+1)/2 | | (y-5)-(6+6)=7y | | x+20=3x-4 | | 18x+27=9x+36 | | c=200+25x | | -2/3y=10.6 | | 2*5x=10*2x | | 5a-10b-10a+6b/2a | | 8x+7=16+5x | | (5a-10b-10a+6b)/2a | | b=1/2*m*p | | -6b+8+4b=-3b+13 | | 28=2[(w+2)+w] | | 2x+240=260 | | -3a+5+4a=11-27 | | 15=7w+2/2+3w+5/4 | | 3R=D+5 | | V=9*6*5 | | (x+4)+(2x-1)=24 | | 10y=4y+10+5 | | 4z+20=3z+3 | | C=2*3.14*7.24 | | (x+15)*3/5-7/12=15 | | x+15*3/5-7/12=15 | | 1/2*23*38=A | | 1/2*23*38 | | -6x+40=31-4x |